Genetic Characteristics of Japanese Clinical Listeria monocytogenes Isolates - Miya, Satoko (PLoS One, 2015)
Listeria monocytogenes causes foodborne illnesses through consumption of ready-to-eat foods. Although 135-201annual listeriosis cases have been estimated in Japan, the details regarding the clinical isolates such as infection source, virulence level, and other genetic characteristics, are not known. In order to uncover the trends of listeriosis in Japan and use the knowledge for prevention measures to be taken, the genetic characteristics of the past human clinical isolates needs to be elucidated. For this purpose, multilocus tandem-repeat sequence analysis (MLTSA) and multi-virulence-locus sequence typing (MVLST) were used in this study. The clinical isolates showed a variety of genetically distant genotypes, indicating they were from sporadic cases. However, the MVLST profiles of 7 clinical isolates were identical to those of epidemic clone (EC) I isolates, which have caused several serious outbreaks in other countries, suggesting the possibility that they have strong virulence potential and originated from a single outbreak. Moreover, 6 Japanese food isolates shared their genotypes with ECI isolates, indicating that there may be risks for listeriosis outbreak in Japan. This is the first investigational study on genetic characteristics of Japanese listeriosis isolates. The listeriosis cases happened in the past are presumably sporadic, but it is still possible that some isolates with strong virulence potential have caused listeriosis outbreaks, and future listeriosis risks also exist.